If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = 2(x + -5) Reorder the terms: -4 + 3x = 2(x + -5) Reorder the terms: -4 + 3x = 2(-5 + x) -4 + 3x = (-5 * 2 + x * 2) -4 + 3x = (-10 + 2x) Solving -4 + 3x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 3x + -2x = -10 + 2x + -2x Combine like terms: 3x + -2x = 1x -4 + 1x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 1x = -10 + 0 -4 + 1x = -10 Add '4' to each side of the equation. -4 + 4 + 1x = -10 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = -10 + 4 1x = -10 + 4 Combine like terms: -10 + 4 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 15k^2+8k-16=-4 | | (x/3)-6=(x/5)-4 | | 2x^2(x+2)=5(x^2+10x-5) | | 5+4ln(x)=37 | | 4r^2+25r+25=0 | | 5+4lnx=37 | | 5.2x-3.8=6.9x+13.7 | | x+30/8=(1/4)x | | 3x+5-7x+8= | | 49b^2-42b-16=0 | | 4m+95m-12=42 | | n^2-11n+26=-4 | | r^2-5r-8=-8 | | a=-1bx-1y+cx-1z | | 5-(6^1/3)/(7^5/3)+(28^1/4) | | (5-(6^1/3))/((7^5/3)+(28^1/4)) | | (5-6^1/3)/(7^5/3+28^1/4) | | 5-6^1/3/7^5/3+28^1/4 | | x-7=128.93 | | 5x^2-15x+45=0 | | 3X-2whenX=6 | | -9*5/2-4+12/3+7 | | 2x^2-8x+9=9 | | 10x-125=7x-5 | | Y=x^3-4x^2-13x-8 | | 2x^2+8x+9=9 | | 7x-3+2x=3x+11 | | 7x-3+2=3x+11 | | 2014-1950= | | 5/9a-4=8.33333 | | 27x-13=257 | | 26=9y+(-1) |